The effectiveness of gender-based violence prevention among adolescents aged 10 to 19 years in Southeast Asia: a systematic review - Hoa Hong Nguyen; Kien G. To; Van T. H. Hoang; Lu Gram; Kathryn M. Yount (International Journal for Equity in Health)
Abstract Background Gender-based violence (GBV) is a major public health problem with wide-ranging negative physical and mental health consequences for survivors. The global economic costs of GBV are estimated at US$1.5 trillion. Adolescence is a high-risk period for GBV. The evidence-based GBV prevention programs among adolescents in Southeast Asia are not well understood. This paper synthesizes GBV prevention intervention studies in this region’s adolescents aged 10–19 years. Methods A systematic review was conducted following the PRISMA guidelines. PubMed, Medline, Embase, Web of Science, and PsycINFO were used to search for potential articles published up to September 3, 2024. We screened and identified articles following consistent inclusion and exclusion criteria. We assessed the risk of bias using the ROBINS-I tool for observational and quasi-experimental studies and the RoB 2 tool for randomized controlled trials. Results Seven of 1689 identified articles were included in the review (four quasi-experimental designs, two pre-test and post-test designs, and one cluster randomized controlled trial). Most studies (6/7) focused on school-based educational programs. The risk of bias in the cluster randomized controlled trial was “some concern” level, compared with the moderate to serious level of the non-randomized studies. One pre- and post-test study directly measured GBV behaviour and found that children reported fewer experiences of physical assault (mean difference: 1.1; 95% CI: 0.6, 1.6) and psychological aggression (1.5; 0.8, 2.3) after the intervention. The remaining studies evaluated the knowledge, attitudes, and skills of participants as primary outcomes in sexual violence prevention programs. Three of the five studies that assessed changes in knowledge showed significant improvements. Inconsistent findings were found in association with attitudes and skills of GBV intervention prevention programs. Conclusions GBV intervention studies among adolescents in Southeast Asia are rare, and evidence of effectiveness is generally weak. Rigorous RCTs that assess program impacts on GBV behaviour, as well as knowledge, attitudes, and skills, are needed. Programs that incorporate classroom activities and online learning with Facebook/Zalo/Instagram assignments and games may show promise for rigorous evaluation in Southeast Asia. Registration : This systematic review was registered on PROSPERO (CRD42023476059).